Pengaruh Kadar Filler Mikrokristalin Selulosa Dan Plasticizer Gliserol Terhadap Sifat Dan Morfologi Bioplastik Berbasis Pati Sagu - Hendri, Zwilla Oktoriana; HS, Irdoni; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Bioplastic is one of alternative solution to change comercial plastic that can be dangerous to environment. Bioplastic can make degradation become easier. One of potential raw materialis sago because it has a highest starch component. The general aims of this research are the study of impact Microcrystalline cellulose filler and plasticizer glycerol to mechanicalproperties and morphology of bioplastic. The synthesis method is casting of starch, water, filler and plasticizer with composisition of filler is (4-12 % b/b), composisition of plasticizer (10–22 % b/b), and composisition of water (100-150 ml). The analysis of bioplastic is tensile strenght, elongation, modulus young, hidrophobicity (water uptake), biodegradation, SEM (Scanning Electron Microscopy), and design expert v.10.0.1 trial version. The most react variable is the composition of filler, followed by plastcizer glycerol and water ratio. The best process condition is bioplastic with composisition filler 12 %b/b, plasticizer 10 % b/b, andwater compotition 100 ml with the value is tensile strenght 14,21 Mpa, elongation 36,91%, water uptake 36,91%, and biodegradation 34,43%. Micrograf analysis shows that fillerdistribution is not equally on sago starch matrices and stil has a clod.Keywords : bioplastic, casting, filler, plasticizer, water uptake